Gods in the public sphere: political deification in South Asia - Sen, Moumita (Religion, 2022)
This article proposes the idea of ‘political deification’ as a useful analytical concept to theorize the efficacy of religious icons, symbols, and objects in the political field of social movements and electoral politics in South Asia. This article uses the insight from various ethnographic studies to understand comparatively what political deification does, that is, what it is productive of. Some forms of political deification operate at the scale of the nation and sovereign authority; other forms operate at the scale of more localised caste-based communities within relatively established political orders; while yet other forms are scaled in ways that enable them to partake in countercultural formations that work to bring new political communities into being in opposition to an established order. We argue that political deification is fundamentally productive of political communities at different scales, in different contexts, and different parts of South Asia.